1998
DOI: 10.1074/jbc.273.52.35147
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p47 , a Cytosolic Subunit of the Leukocyte NADPH Oxidase

Abstract: The leukocyte NADPH oxidase catalyzes the reduction of oxygen to superoxide (O 2 . ) at the expense of PHOX to the membrane at some point after the first phosphorylation takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…In an earlier study in which phorbol myristate acetate, an activator of PKC, was used to stimulate the neutrophils, we found that phosphorylation of one of the pairs (S303, S304) together with another of the pairs (S359, S370) was necessary for oxidase activation (19,20). PKC did not phosphorylate S328.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study in which phorbol myristate acetate, an activator of PKC, was used to stimulate the neutrophils, we found that phosphorylation of one of the pairs (S303, S304) together with another of the pairs (S359, S370) was necessary for oxidase activation (19,20). PKC did not phosphorylate S328.…”
Section: Discussionmentioning
confidence: 99%
“…We previously have explored the manipulation of several serines identified as targets for phosphorylation during NADPH oxidase activation (19,20), and, with the current findings, it will be important to explore the functional role of S304 and S328 further.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, phosphorylation induces a conformational change in p47 phox , which unmasks the tandem SH3 domains, thereby allowing binding to p22 phox and translocation to the membrane. Babior et al (26) have shown that phosphorylation of Ser-359 or Ser-370 is absolutely required for translocation as well as oxidase activity. Interestingly, both of these serines are adjacent to the poly-proline motif, which is the target of the C-terminal SH3 domain of p67 phox , suggesting that phosphorylation might interfere with this interaction and may potentially induce the release of p67 phox rendering this sequence accessible for p40 phox .…”
Section: Discussionmentioning
confidence: 99%
“…2A). Interestingly, the homologue was missing the proline-proline-argininearginine-containing region of p47 phox , which is involved in autoinhibition (17) through binding to the N-terminal SH3 domain, as well as the adjacent serine phosphorylation sites (18), which relieve autoinhibition when phosphorylated (19). This suggested a stimulus-independent activity of the homologue.…”
Section: Cloning Of Mouse P47mentioning
confidence: 99%